Assessing kinematics and kinetics of high-speed running using inertial motion capture: a preliminary analysis - Chatterton, G. J.; Hansen, J. B.; Kristiansen, N. H.; Kunwald, N. P.; Kersting, U. G.; Oliveira, A. S. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to determine whether inertial motion capture (IMC) in combination with musculoskeletal modeling is a suitable method to assess lower limb kinematics and kinetics during high-speed running. Optical motion capture (OMC), IMC and ground reaction forces (GRF) were used as input for musculoskeletal models. Kinematics showed excellent correlations (knee: 0=0.98, rRMSE=21.0%, hip: 0=0.95, rRMSE=18.5 %, ankle: 0=0.93, rRMSE=46.6%). The ground reaction force predictions showed varying results (anteroposterior: 0=0.77, rRMSE=33.4%, mediolateral: 0=0.04, rRMSE=69.1%, vertical: 0=0.78, rRMSE=25.7%). The examined IMC and musculoskeletal modeling approach was proven a useful alternative to OMC and force plates for outdoor measurements in high-speed running.